Fit-for-purpose solutions beyond supervised injection offer the next stage of harm reduction for the US drug epidemic - Hannah Bard; Avik Chatterjee (Discover Public Health)
Abstract Overdose Prevention Centers (OPCs) provide critical harm reduction services for people who use drugs. For over twenty years, such centers, including supervised injection facilities, have proven to be successful tools for combating drug epidemics with well-demonstrated benefits of reducing overdose deaths and the transmission of infectious disease such as HIV in participating communities in Europe, Australia, and Canada. Although there are limited exceptions in the US, the controversial nature of OPCs has prevented adoption across the country, thereby contributing to large numbers of preventable deaths. Analysis of CDC overdose death data demonstrates that the drug types causing deaths are highly variable by state and that while opioids (primarily fentanyl) are the most important contributor, a significant portion of overdose deaths do not involve opioids and are likely to involve other modes of consumption in addition to injection. Considering this finding, arguments are made for policy and facility strategy changes that would lead to development of new fit-for-purpose OPCs that are best suited to specific regions and likely more acceptable to individuals within these communities. Tailoring OPCs could accelerate destigmatization and increase adoption of OPCs in urban and non-urban communities to effectively manage this nationwide epidemic.